Short Communication: Activity budget and diet in silvery lutung Trachypithecus cristatus at Gunung Padang, West Sumatra, Indonesia - MUHAMMAD AZHARI AKBAR; RIZALDI RIZALDI; WILSON NOVARINO; DYAH PERWITASARI-FARAJALLAH; YAMATO TSUJI (Society for Indonesian Biodiversity, 2019)
Abstract. Akbar MA, Rizaldi, Novarino W, Perwitasari-Farajallah D, Tsuji Y. 2019. Activity budget and diet in silvery lutung Trachypithecus cristatus at Gunung Padang, West Sumatra, Indonesia. Biodiversitas 20: 719-724. We studied the activity budget and diet of a group of wild silvery lutungs (Trachypithecus cristatus) in Gunung Padang, West Sumatra, Indonesia, with special attention to age-and sex-related differences. We conducted behavioral observations between July and October 2016, and found that resting constituted the greatest proportion of their daily activities (46%), followed by moving (38%), feeding (12%), and grooming (4%). Resting peaked between 11 am and 1 pm, while moving decreased in this period. The juveniles showed higher percentage of moving and lower percentage of feeding than the adults. The adult males showed higher percentage of grooming than the adult females. Finally, the nursing females showed lower percentage of resting and higher percentage of grooming than single females. During the study, we recorded 14 plant species consumed by the lutungs. Their dietary composition was composed of 63% foliage and 37% fruit. Both the foliage and fruits of Ficus variegata, a plant species belonging to the family Moraceae, was the most consumed. Foliage was frequently consumed by the nursing females and juveniles. The adult males were frequently observed to eat fruit during the study period. No fruit was consumed by the nursing females.